Level of Elderly Participation in Recreational Soccer Activities: A Study of Arnstein's Ladder of Participation - RACHMAD IRFAN NUR MALIKI; Heny Setyawati (Journal of Physical Education and Sports, 2026)
This study aims to analyze the level of participation of older adults in recreational soccer activities based on Arnstein's Ladder of Citizen Participation (1969). Given the rapid growth of the older adult population in Indonesia, this study is important to support sustainable active aging strategies. A descriptive qualitative approach was used with 8 active elderly participants aged 60-65 years in Kediri Regency, specifically at the Mitra Muda Blabak and Amphibi Sambi clubs. Data were collected through in-depth interviews, participatory observation, and documentation over a period of 2-4 weeks, then analyzed using the Miles and Huberman model. The results showed that 75% of participants fell into the Citizen Power category, 25% into the Tokenism category, and none into the Non-Participation category. These findings indicate that recreational soccer serves as an effective means of social empowerment for older adults, supporting the principle of active aging. However, the presence of tokenism among some participants indicates the need for greater delegation of authority in decision-making. It is recommended that the development of sports programs for older adults focus more on strengthening participant agency and social integration to improve their quality of life in a sustainable manner and reduce participation gaps. Policy implications are needed to ensure more equitable access for older adults to community physical activities.